PENGGUNAAN ALAT MUSIK GAJEUMA’DALAM MASYARAKAT DI DESA MUNTEIKECAMATAN SIBERUT KABUPATEN KEPULAUAN MENTAWAI - Susirawati Susirawati; Jagar Lumban Toruan; Marzam Marzam (SENDRATASIK UNP, 2013)
Abstract   The research aimed at describing the use of music instrument Gaejuma in the society of Mentawai at Siberut Selatan Mentawai. Such traditional arts possessed by the society included vocal music, traditional music instruments and daily traditional dances. The three traditional arts were closely related to social activities such as wedding party, the coronation of shaman, the expansion of new farming area, the construction of new houses and the medication of people. One of the traditional music which was always performed during the local ceremonies in Mentawai was the music instrument Gaejuma. The performance of Gaejuma in every ceremony was to tone up the ceremonies like in the wedding party, to cure those who were sick or ill, to remove the bad spirits during the expansion of new farming area or the construction of new houses, during the coronation. Keywords: The use, Gaejuina, Social activities